Oxidative dissolution of metals in metal-based ionic liquids: Iron, copper, silver and aluminum - Yuchao Li; Yanxia Zheng; Huishuang Zhao; Qingshan Zhu; Yansong Zhao (Journal of Ionic Liquids)
Recycling of metals from end-of-life products requires an essential step of metal and alloy dissolution. Metal-based ionic liquids have the potential to be used for this purpose. However, scant work has been reported on oxidative dissolution of metal and alloys using metal-based ionic liquids. In this work, oxidative dissolution of four metals (Fe, Cu, Al and Ag) in pure metal-based ILs and aqueous IL is investigated. It is found that pure [Bmim][FeCl4] has no significant corrosion on steel. However, steel ball and copper can be dissolved into 20 % [Bmim][FeCl4] aqueous solution. Meanwhile, iron and copper powder can be quickly dissolved into [Bmim][CuCl3] and [Bmim][AgCl2] aqueous solution. Therefore, our results suggest that metal-based ionic liquid can be utilized to dissolve metal from mines using aqueous metal-based ionic liquid and then metal can be deposited from metal-rich aqueous metal-based ionic liquid water by removing water. By this method, high purified metal can be extracted from mines. In addition, with the increasing amount of electrical cars/buses, battery waste will be a big problem in the next 5–10 years. Our results manifest that a promising method for metal extraction from battery waste.